A 44-YEAR-OLD MAN WITH BRONCHIAL ASTHMA: CASE REPORT (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Bronchial asthma is a chronic disease characterized by shortness of breath, wheezing, chest tightness and coughing. Asthma cannot be cured, but it can be controlled to reduce and prevent asthma attacks. According to the World Health Organization, bronchial asthma affected around 262 million people in 2019 and caused 455.000 deaths. This case report describes a 44-year-old man, who came to the emergency room with complaints of shortness of breath and felt intermittent since the last two months and worsen one day before entering the hospital. Shortness of breath accompanied by complaints of coughing, fever, and wheezing. The patient has a history of asthma since he was a teenager. In the past month, asthma symptoms have been felt almost every day, often waking up at night, and there are limitations in doing activities when asthma relapses. Complaints of shortness of breath felt better after taking the fenoterol inhalation drug. On examination of vital signs obtained a temperature of 38.1oC, 95% oxygen saturation, chest auscultation examination found wheezing during expiration. Routine blood laboratory examinations, normal results were obtained, whereas in chest X-rays, increased bronchovascular markings were found, suggesting a picture of bronchitis. The therapy given to the patient was in the form of oxygen nasal cannula 2 liters per minute, omeprazole IV injection 40 mg every 12 hours, ceftriaxone IV injection 2 grams every 24 hours, methylprednisolone IV injection 62.5 mg every 24 hours, acetylcysteine ​​1 capsule every 8 hours, paracetamol tablets every 8 hours if you have a fever, as well as nebulized Salbutamol – Ipratropium Bromide – Budesonide. During treatment the patient's condition improved. The patient was then allowed to be outpatient and given Formoterol – Budesonide inhalation therapy twice a day, one puff.
Keywords: asthma; therapy; symptoms; shortness of breath